Clinical research in occupational therapy - Stein, Franklin; Rice, Martin S; Tomlin, George (Routledge New York, 2024)
"In this new edition, Dr. George Tomlin joins Dr. Martin S. Rice and Dr. Franklin Stein to add expertise and knowledge of the occupational therapy field. With the combined knowledge and skills of the authors, Clinical Research in Occupational Therapy, Sixth Edition includes many valuable updates and enables the graduate student and clinical researcher to carry out a research study from the formulation of a research hypothesis to collecting, analyzing, and interpreting data in user-friendly, step-by-step procedures. This Sixth Edition brings noteworthy changes, improvements, and enhancements, including the following: - A thorough update of the published research in occupational therapy and health care - Major revisions in all the chapters - The addition of a new chapter on single-case experimental research - Updated research boxes and contemporary examples of both quantitative and qualitative research - Updated compilation of tests and evaluations used by occupation therapists in research studies as outcome instruments and for clinical assessments - Revision and additions to the glossary of terms and statistics - Updated examples of the institutional review board application forms - Updated landmarks in the history of occupational therapy - Updated interfacing example with a popular statistical software, including data organization analysis and interpretation - Updated statistical tables"--Provided by publisher.
Franklin Stein's name appears first in previous edition.
Includes bibliographical references.
Keywords: Occupational Therapy; Biomedical Research -- methods; Research Design